Genetically engineered food : (Wiley-VCH, 2003)
Application and Perspectives -- Transgenic Modification of Production Traits in Farm Animals -- Genetically Modified Plants -- Fermented Food Production using Genetically Modified Yeast and Filamentous Fungi -- Production of Food Additives using Filamentous Fungi -- Perspectives of Genetic Engineering of Bacteria used in Food Fermentations -- Legislation in Europe -- The Legal Situation for Genetically Engineered Food in Europe -- Methods of Detection -- Detection of Genetic Modifications: Some Basic Considerations -- DNA-based Methods for Detection of Genetic Modifications -- Genetic Engineering of Fishes and Methods for Detection -- Detection Methods for Genetically Modified Crops -- Methods to Detect the Application of Genetic Engineering in Composed and Processed Foods -- Mutations in Lactococcus lactis, and their Detection -- Detection Methods for Genetically Modified Microorganisms used in Food Fermentation Processes.